The Human Rights-Based Approach to STEM Education - Tajmel, Tanja; Starl, Klaus; Spintig, Susanne (Waxmann Verlag, 2021)
This volume provides the first introduction to the right to science/STEM education, with contributions from international scholars and experts from organizations, including UNESCO, and from diverse disciplines such as human rights; science education; educational studies; anti-racist and decolonizing pedagogy; feminist and gender studies in science, technology, and engineering; and management and organizational studies. The book offers a thorough grounding in the right to education and its application in the STEM fields. It provides interdisciplinary perspectives that allow for a broad understanding of the human right to science education at all intersectional levels of STEM education and in STEM careers. Based on the Berlin Declaration on the Right to Science Education, adopted at the 1st International Symposium on Human Rights and Equality in STEM Education (October 2018), this volume suits as a textbook for university courses at the undergraduate or graduate level. It will also prove extremely valuable to researchers from a range of disciplines but, in particular, those interested in human rights, education, science/STEM education, as well as practitioners, program and curriculum developers, policy makers, educators, and, of course, the interested public.